2022
DOI: 10.1371/journal.pone.0267847
|View full text |Cite
|
Sign up to set email alerts
|

Whole genome sequencing of SARS-CoV2 strains circulating in Iran during five waves of pandemic

Abstract: Purpose Whole genome sequencing of SARS-CoV2 is important to find useful information about the viral lineages, variants of interests and variants of concern. As there are not enough data about the circulating SARS-CoV2 variants in Iran, we sequenced 54 SARS-CoV2 genomes during the 5 waves of pandemic in Iran. Methods After viral RNA extraction from clinical samples collected during the COVID-19 pandemic, next generation sequencing was performed using the Nextseq platform. The sequencing data were analyzed an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 54 publications
4
32
0
Order By: Relevance
“…Ligand binding, viral oligomerization and packaging, fusion and antibody sensitivity have been reported to be disturbed by these mutations ( Arya et al, 2021 ; Ahamad et al, 2022 ). Moreover, our findings stand in good agreement with the proposal that in addition to the D614G substitution, mutations in the N protein (R203K/G204R mutations) affect infectivity and virulence of SARS-CoV-2 ( Wu S. et al, 2021 ; Yavarian et al, 2022 ). Therefore, future vaccine development programs may also focus on regions other than the Spike protein.…”
Section: Discussionsupporting
confidence: 91%
“…Ligand binding, viral oligomerization and packaging, fusion and antibody sensitivity have been reported to be disturbed by these mutations ( Arya et al, 2021 ; Ahamad et al, 2022 ). Moreover, our findings stand in good agreement with the proposal that in addition to the D614G substitution, mutations in the N protein (R203K/G204R mutations) affect infectivity and virulence of SARS-CoV-2 ( Wu S. et al, 2021 ; Yavarian et al, 2022 ). Therefore, future vaccine development programs may also focus on regions other than the Spike protein.…”
Section: Discussionsupporting
confidence: 91%
“…V and L clades were discovered during the first wave; G, GH and GR clades identified the second wave; GH and GR were circulating clades during the third wave; and GRY (α variant), GK (δ variant) and one GH clade (β variant) were discovered in the fourth wave. All of the viruses in the fifth wave belonged to the clade GK (δ variant) [ 28 ]. The genomes in the current study were mostly from the clades GH (25%), GR (23%), O (21%) and GRY (14%).…”
Section: Discussionmentioning
confidence: 99%
“…In the last updates of SARS‐CoV‐2 from 54 sequencing of 5 waves in Iran, different mutations were found in various sections of the genomes. However, the most common mutants were found in the Spike‐D614G, N‐R203K, N‐G204R and NSP12‐P323L 8 . Further analysis of SARS‐CoV‐2 sequencing confirmed that multiple mutations in the genome concentrated in the open reading frame area and SPs 9–11 .…”
Section: Introductionmentioning
confidence: 94%
“…However, the most common mutants were found in the Spike‐D614G, N‐R203K, N‐G204R and NSP12‐P323L. 8 Further analysis of SARS‐CoV‐2 sequencing confirmed that multiple mutations in the genome concentrated in the open reading frame area and SPs. 9 , 10 , 11 The most important variants and mutations ( https://covariants.org/ ) regarding viral infectivity were found in SPs at the position of 614 (D614G) (see Figure 1 ).…”
Section: Introductionmentioning
confidence: 97%